Asymmetric gradient sintering composite medium as well as preparation process and application thereof

By using asymmetric gradient sintered composite media in the sintered filter element, combined with polyethylene substances and appropriate structural parameters, the problem of insufficient bonding strength of the existing sintered filter element is solved, and efficient interception and high throughput balance is achieved. Improves service life and pressure resistance.

CN119459074AActive Publication Date: 2025-02-18HANGZHOU COBETTER TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411382748.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-18
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

While taking into account high retention efficiency and high throughput, existing sintered filter elements have problems such as insufficient bonding strength, easy separation and short service life, especially when used under high pressure.

Method used

Using asymmetric gradient sintering composite media, the structural design of the support layer, composite layer and separation layer is combined with the use of polyethylene materials to ensure that the composite media has appropriate pore size and porosity, and through the thickness of the composite layer and the separation layer Crystalline degree to improve binding strength.

Benefits of technology

It achieves the improvement of the bonding strength and service life of the composite medium on the basis of high interception efficiency and high throughput, can be used normally under higher pressure, and is suitable for the recovery of catalysts and precious metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119459074A_ABST
    Figure CN119459074A_ABST
Patent Text Reader

Abstract

The invention discloses an asymmetric gradient sintering composite medium as well as a preparation process and application thereof. The composite medium comprises a supporting layer, a composite layer and a separation layer for intercepting various fine substances, wherein the separation layer comprises first particles for forming a porous structure; the supporting layer comprises second particles for forming a porous structure, and the composite layer comprises first particles and second particles for forming a porous structure; the first particles and the second particles are polyethylene substances; the thickness of the composite layer is not less than 0.1 mu m, and the crystallinity of the separation layer is 40-85%; the PMI average pore size of the composite medium is 0.1-25 [mu] m, and the overall porosity is 25-75%; the whole composite medium has proper aperture and porosity, and has the composite layer with certain thickness, so that the composite medium has high composite strength while having high interception efficiency and high flux, and the separation layer and the support layer are not easy to separate during long-time work; the method is especially suitable for recycling catalysts and precious metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of porous sintered materials, and in particular to an asymmetric gradient sintered composite medium and a preparation process and application thereof. Background Art

[0002] Sintering is an important material preparation process. Sintering refers to the process in which solid powder particles are physically formed, then begin to melt and adhere under the condition of heating to a certain temperature, and finally form a sintered porous material with a certain shape and performance.

[0003] For example, a Chinese patent with publication number CN103071400A, a method for producing a microporous membrane sintered filter element (applied by Ningbo Aiquou Water Purification Equipment Technology Co., Ltd.), discloses a sintered filter element made of ultra-high molecular weight polyethylene as the main raw material, which forms a microporous structure through physical hot melt bonding. The average pore size of the sintered filter element is 0.28μm, and it has good retention efficiency and high retention accuracy for impurity particles; but similarly, due to the relatively small average pore size of the above-mentioned sintered filter element, while having high retention accuracy and high retention efficiency, the flux of the above-mentioned sintered filter element is often relatively low, that is, the single-layer sintered filter element in the above-mentioned patent usually cannot take into account both high retention efficiency and high flux, which limits the application scope of the above-mentioned sintered material.

[0004] Furthermore, those skilled in the art think of preparing a sintered composite material in a composite form based on a single-layer sintered material with a higher flux. Such a composite material generally includes a separation layer and a support layer, wherein the separation layer is used to ensure the interception efficiency, and the support layer is used to improve the flux, thereby making the sintered composite material have both high interception efficiency and high flux. In general, those skilled in the art at least hope that the types of sintered materials used to form each layer are the same (such as all organic materials, and further, for example, all polyolefin materials), because if even the types of materials in each layer are different (for example, one is an organic material and the other is an inorganic material), their compatibility will be very poor, and it is easy to cause the sintering to be affected by factors such as the interfacial tension between different substances. The bonding strength of the composite material is extremely poor, that is, the support layer and the separation layer are easily separated under a relatively small pressure, normal filtration cannot be performed, and the particles of each layer are relatively easy to fall off; and even if the sintered material types used to form the support layer and the separation layer in the sintered composite material are the same (for example, both are PE-type materials) and have a certain compatibility, there is still a problem of relatively poor bonding strength, which can still easily lead to the support layer and the separation layer in the sintered composite material being easily separated from each other, and even "powder inclusions" in some areas. The overall compressive strength and hardness of the sintered composite material are not high, which in turn shortens the service life of the sintered composite material, especially it cannot be used under higher pressure, let alone backwashing, which greatly affects the application range of the sintered material. Summary of the invention

[0005] The purpose of the present invention is to provide an asymmetric gradient sintered composite medium and its preparation process and application. The composite medium includes a support layer, a composite layer and a separation layer for intercepting various fine substances; the composite medium as a whole has a suitable pore size and porosity, and at the same time has a composite layer of a certain thickness, thereby ensuring that the composite medium has high interception efficiency and high flux while also having high composite strength (the separation layer and the support layer are not easy to separate); it is particularly suitable for use in the recovery of catalysts and precious metals (platinum and iridium, etc.).

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] An asymmetric gradient sintered composite medium comprises a main body, wherein the main body has a non-directional tortuous passage, the main body comprises a support layer, a composite layer and a separation layer for intercepting various fine substances; the composite layer is located between the support layer and the separation layer; the average pore size of the separation layer is smaller than the average pore size of the support layer;

[0008] The separation layer includes first particles for forming a porous structure; the support layer includes second particles for forming a porous structure; the composite layer includes first particles and second particles for forming a porous structure; the first particles and the second particles are both polyethylene materials;

[0009] The thickness of the composite layer is not less than 0.1 μm, and the crystallinity of the separation layer is 40%-85%;

[0010] The average pore size of the PMI of the composite medium is 0.1-25 μm, and the overall porosity of the composite medium is 25%-75%.

[0011] The composite medium of the present invention can be mainly divided into three regions along the thickness direction, namely, a support layer, a composite layer and a separation layer; the pores in the support layer have a larger pore size, which is mainly formed by sintering the second particles; the pores in the separation layer have a smaller pore size (the average pore size of the separation layer is smaller than the average pore size of the support layer), which can be used to intercept various fine substances and are formed by sintering the first particles; the composite layer is located between the support layer and the separation layer, and the first particles and the second particles coexist in the composite layer. The composite layer can be understood as the support layer and the separation layer being formed by mutual penetration; therefore, the thickness of the composite layer is limited (not less than 0.1 μm), It directly reflects that the bonding depth between the support layer and the separation layer will not be too low, ensuring that there is a certain bonding strength basis between the support layer and the separation layer. Under normal circumstances, the higher the penetration bonding depth between the support layer and the separation layer, that is, the thicker the composite layer, the higher the bonding strength, and the less likely it is to separate (it can also be used normally under higher pressure); at the same time, since the first particle and the second particle are both polyethylene materials (with certain similar compatibility), it is easier to composite, ensuring the composite strength, and then further making the composite medium have a longer service life, meeting various applications, and the layers are not easy to separate during backwashing;

[0012] According to the prior art, the average pore size of PMI can reflect the size of the overall pore size in the composite medium to a certain extent. The larger its value is, the larger the overall pore size of the composite medium is. The size of its value (its value is mainly determined by the size of the pores in the separation layer) greatly affects the interception efficiency of the composite medium for various impurities. In the present invention, the average pore size of PMI of the composite medium is 0.1-25 μm (the composite medium is a microporous medium with relatively large pores), and its performance is essentially different from that of nano-porous materials. The composite medium of the present invention ensures that the composite medium can fully and effectively intercept impurity particles of a certain particle size (mainly micron-level impurities) through the synergistic effect of a certain average pore size of PMI and a non-directional tortuous path (the non-directional tortuous path refers to a randomly oriented groove structure and / or a discretely distributed pore structure, and each non-directional tortuous path is interconnected) with high interception efficiency.

[0013] Commonly used porosity testing methods include mercury injection method, density method and weighing method, etc. Of course, those skilled in the art can also obtain the above parameters by other measuring methods, and the above measuring methods are for reference only. After testing, the overall porosity of the composite medium of the present invention is 25%-75%, which indicates that the porosity of the composite medium is relatively large, the number of holes is large, and it is conducive to high flux. Through the synergistic effect of the PMI average pore size and the overall porosity of the composite medium, it is ensured that the composite medium has a high flux, a fast filtration speed, and a high dirt holding capacity, and can intercept more impurity particles and a long service life. At the same time, under the synergistic cooperation of the separation layer with appropriate crystallinity, it is ensured that the mechanical properties of the composite medium are still high.

[0014] Under normal circumstances, technicians in this field generally believe that the higher the crystallinity of the separation layer, the better. This is because the higher the crystallinity, the more crystal regions, the better the degree of lattice molecular orientation, and the better its mechanical strength. Then the composite strength and compressive strength of the entire composite medium will be higher. However, the actual situation is not that the higher the crystallinity of the separation layer, the higher the mechanical strength of the entire composite medium and the bonding strength between the separation layer and the support layer. Instead, the crystallinity of the separation layer is controlled within an appropriate range and cannot be too high, because too high a crystallinity will affect the interfacial tension between the separation layer and the support layer, thereby increasing the interfacial tension between the two, which is not conducive to improving the bonding strength between the two. In addition, if the crystallinity of the separation layer is too high, it means that the degree of lattice orientation at the interface between the separation layer and the support layer is higher, which may also make it more difficult for the support layer and the separation layer to penetrate each other, further reducing the bonding strength between the two. , and even the phenomenon of "powder inclusion" may occur; the DSC crystallinity of the separation layer in the present development is 40%-85%, and the separation layer has such a crystallinity based on a certain pore size and a certain porosity of the present invention (the determination of the crystallinity of the nano-scale composite medium is completely different from the present invention); under the effect of such crystallinity, on the one hand, it is ensured that the composite medium can also have good mechanical strength, so that the stability of various properties of the composite medium can be guaranteed when dealing with working conditions; at the same time, it is found that under the synergistic effect of the appropriate separation layer crystallinity and the thickness of the composite layer, there are more non-directionally arranged areas in the composite layer, and the non-directionally arranged areas are more likely to penetrate each other, which promotes the combination between the separation layer and the support layer, reflecting that the support layer and the separation layer have good bonding strength, and better solve the problem that the conventional composite layer structure is easy to separate. The composite medium of the present invention is not easy to separate under the action of backwashing, and there is no phenomenon of easy falling off of particles;

[0015] In the present invention, the structural arrangement of the support layer, the separation layer and the composite layer, and the average pore size and porosity of the composite medium are within a suitable range, combined with the crystallinity of the separation layer within a suitable range, so that the pore structure of the separation layer and the composite layer can have good stability under a certain pressure, and can ensure that the pores are not prone to collapse during fluid filtration, thereby ensuring that the composite medium has a high flux and excellent interception efficiency, and is also beneficial to maintaining the bonding strength of the composite layer, and separation is not easy to occur between the support layer and the separation layer; at the same time, the entire composite medium also has a high mechanical strength (high compressive strength and hardness); under the combined influence of the composite medium having such an average pore size and porosity and a certain degree of crystallinity of the separation layer, as well as a certain thickness of the composite layer, it is also found that the composite medium also has an unexpected technical effect, that is, it has a technical effect of relatively slow flux attenuation and not prone to clogging (high dirt holding capacity), which is probably because the pore size of the composite medium does not change too fast with thickness and has a suitable change gradient.

[0016] The PMI average pore size of the composite medium in the present invention is obtained by testing with a PMI pore size tester; the DSC crystallinity of the composite medium can be obtained by differential scanning calorimetry.

[0017] As a further improvement of the present invention, the SEM average particle size of the first particles is 5-60 μm, and the SEM average particle size of the second particles is 80-500 μm.

[0018] In powder sintering, the pore size of the sintering medium is closely related to the particle size of the powder particles. Generally, powder particles with relatively small particle sizes are more likely to form relatively small pores under certain sintering effects. Since the separation layer is mainly used to intercept various tiny impurity particles, the pore size inside it is relatively small, so the particle size of the first particles (several first particles are sintered to form a separation layer) is not expected to be too large. After sintering, the average particle size of the first particles under SEM should be controlled at 5-60μm. Under such a particle size, the separation layer can be guaranteed to have a There is a suitable pore size to ensure the interception efficiency; on the other hand, combined with the separation layer having a suitable DSC crystallinity, the number of pores in the separation layer is ensured not to be too small, which will not affect the flux of the composite medium, and at the same time, it is beneficial to have a high yield of impurities in the subsequent backwashing process; at the same time, the particle size of the first particles will not be too small, because research has found that if the particle size of the first particles after sintering is too small, the binding effect between the first particles may not be strong enough, and they are easy to fall off during long-term filtration, especially backwashing, which not only affects the purity of the fluid, but also greatly shortens the service life of the composite medium;

[0019] The support layer is a macroporous structure, so the particle size of the second particles (several second particles are sintered to form a support layer) needs to be relatively large. After sintering, the SEM average particle size of the second particles should be controlled at 80-500μm. Under such a particle size, on the one hand, it can ensure that there are holes with larger pores in the support layer, the number of holes is large, and the porosity of the support layer and even the composite medium is high; at the same time, the second particles can be considered as the "skeleton" inside the support layer. If its value is too small, it will greatly affect the stability of the holes in the support layer. During high-pressure filtration, the holes in the support layer are prone to collapse and deformation, making the entire composite medium unable to continue to be used; when the second particles after sintering have a suitable particle size, it can ensure the compressive strength inside the support layer, and then ensure that the entire composite medium has a high mechanical strength;

[0020] After sintering, the first particles and the second particles of a certain particle size work together to further enable the composite medium to have a good flux and high interception efficiency, while having high compressive strength and hardness.

[0021] The SEM average particle size of the first particles and the second particles in the present invention can be measured by using a scanning electron microscope to characterize the morphology of the cross section of the sintered porous medium, and then using computer software (such as Matlab, NIS-Elements, etc.) or manually, and performing corresponding calculations; when actually measuring, the cross section (thickness direction) of the sintered porous medium can be characterized by an electron microscope to obtain a corresponding SEM image, and since the distribution of the first particles and the second particles in the sintered porous medium on the cross section is roughly uniform, a certain area, such as 1 μm, can be selected. 2 (1μm times 1μm) or 100μm 2 (10 μm multiplied by 10 μm) or, the specific area size depends on the actual situation, and then the SEM average particle size of the first particles and the second particles on the area is measured by corresponding computer software or manually, and several tests are performed (preferably more than 10 times, the specific number of times depends on the situation), and the average value is taken to obtain the SEM average particle size of the first particles and the second particles; of course, those skilled in the art can also obtain the above parameters by other measurement methods, and the above measurement methods are for reference only.

[0022] As a further improvement of the present invention, the thickness of the composite layer is 1-1000 μm, preferably, the thickness of the composite layer is 10-800 μm; more preferably, the thickness of the composite layer is 50-500 μm;

[0023] In the composite layer, connection nodes are formed between the first particles and the second particles, and the SEM average width of the connection nodes is 3-50 μm.

[0024] The composite layer can be understood as the mutual penetration of the support layer and the separation layer. In the composite layer, the first particle and the second particle will exist at the same time (if there is a third particle in the support layer, then the third particle will also exist in the composite layer); the thickness of the composite layer will have a great impact on the bonding strength between the separation layer and the support layer, and then affect the various mechanical properties of the composite medium; if the thickness of the composite layer is too small, the support layer and the separation layer may be separated under a certain pressure, and then affect the filtration efficiency, especially during the backwashing process, and because the separation layer is relatively thin, the separation layer and the support layer are more likely to separate or some particles fall off; by selecting a suitable composite layer thickness, and under the joint action of the first particle and the second particle of the appropriate particle size, it is further ensured that the support layer and the separation layer are tightly bonded, and can adapt to long-term high-efficiency filtration; at the same time, the composite layer will not be too thick, ensuring that the composite medium has a good porosity as a whole, and then has a good flux;

[0025] At the same time, in the composite layer, there are strip structures such as wire-like connecting ribs or overlapping nodes between some adjacent first particles and second particles. We call them connecting nodes. The connecting nodes are used to further connect the first particles and the second particles, which in turn affect the bonding strength between the separation layer and the support layer. Connecting nodes of a certain thickness are beneficial to further improve the composite strength of the composite medium. At the same time, the first particles and the second particles are not easy to fall off under high pressure. The preferred thickness selection of the composite layer further ensures that the composite strength of the composite medium is high, and it has high compressive strength and hardness.

[0026] The characteristics such as the SEM average width of the connection node in the present invention can be obtained by using a scanning electron microscope to characterize the morphology of the cross section of the composite medium, then selecting a certain area and using computer software (such as Matlab, NIS-Elements, etc.) or manual measurement to obtain the width of the connection node, taking the average value, and further calculating the corresponding SEM average width; of course, it can be understood that those skilled in the art can also obtain the above parameters by other measurement means.

[0027] As a further improvement of the present invention, the ratio of the SEM average particle size of the second particles to the SEM average particle size of the first particles is 5-30; the ratio of the SEM average width of the connecting node to the SEM average particle size of the first particles is 1:1.1-4.

[0028] After research, it was found that when the ratio of the SEM average particle size of the second particles to the SEM average particle size of the first particles is too small, either the overall flux of the composite medium will be too low (the particle size of the first particles and the particle size of the second particles are both too small), or the interception efficiency will be too low (the particle size of the first particles and the particle size of the second particles are both too large); and when the ratio of the SEM average particle size of the second particles to the SEM average particle size of the first particles is too large, the overall compressive strength and hardness of the composite medium will be too low; especially when backwashing is required, the layers are easily separated and the particles are easily detached; by regulating the ratio of the SEM average particle size of the second particles to the SEM average particle size of the first particles within an appropriate range, it is more conducive to obtaining a composite medium with high flux and high interception efficiency;

[0029] In addition, the present invention further regulates the ratio of the SEM average width of the connecting node and the SEM average particle size of the first particle, thereby further ensuring that the first particle and the second particle are tightly bonded and the particles are not easily separated. Therefore, the layers are not easily separated when a large pressure is applied, and the particles are not easily fallen off, so that the composite bond has a higher bonding strength, and its compressive strength and hardness are both high, and it can be retained and backwashed for a long time, and has a long service life.

[0030] As a further improvement of the present invention, the thickness of the separation layer is 0.1-5 mm, and the ratio of the thickness of the separation layer to the thickness of the composite medium is 1%-20%.

[0031] The separation layer is a region used to intercept various fine impurities. The thickness of the separation layer will have a certain impact on the interception efficiency of impurities. In the prior art, it is generally hoped that the thickness of the separation layer is larger, because if the thickness is too small, it is easy to cause the interception efficiency of the composite medium to be too low. However, in the present invention, it is not desired that the thickness of the separation layer is too large, because if the thickness is too large, on the one hand, it will affect the overall flux of the composite medium; on the other hand, when the composite medium needs to be backwashed, once the separation layer is too thick, it is difficult for the impurities to be flushed out through the backwashing process, and the recovery rate of the impurities will be too low.

[0032] The separation layer of the present invention has a suitable thickness. On the one hand, the interception efficiency is further guaranteed under the joint action of the tortuous passage, so that the separation layer can fully and efficiently capture various impurities; on the other hand, during the backwashing process, since the thickness of the separation layer is not too thick, various impurities in the separation layer can be washed out, and the yield of impurities is high; in addition, by controlling the ratio of the thickness of the separation layer to the thickness of the composite medium, combined with a certain PMI average pore size and porosity of the composite medium, it is ensured that the composite medium still has a high flux, and the compressive strength and hardness are also high, meeting the needs of practical applications.

[0033] The thickness of the separation layer in the present invention can be obtained by using a scanning electron microscope to characterize the morphology of the cross-section of the composite medium, then selecting a certain area and using computer software (such as Matlab, NIS-Elements, etc.) or manually measuring the thickness of the separation layer, taking the average value, and further calculating the corresponding thickness value; of course, it can be understood that those skilled in the art can also obtain the above parameters by other measurement methods.

[0034] As a further improvement of the present invention, the distribution density of the second particles is 1-30 particles / 1mm 2 The composite medium has a gram weight of 0.5-1.2 g / cm 2 .

[0035] The second particles can be considered as the "skeleton" inside the support layer. The size of the second particles ensures the stability of the pores inside the support layer, which is conducive to obtaining a composite medium with high mechanical strength. However, in addition to the particle size of the second particles, the study found that the number of second particles (i.e., distribution density) will also affect the stability of the pores inside the support layer to a certain extent. By regulating the second particles with a suitable number in the support layer, and the synergistic effect of the second particles with a suitable particle size, the support layer has sufficient porosity and strength, and the second particles are tightly combined with each other. The pores can remain stable during long-term interception, filtration and backwashing. In particular, when there are third particles in the support layer, when the porosity is large, it is more necessary to control the number of second particles to ensure that the distribution density of the second particles is within a suitable range.

[0036] Gram weight can also be considered as surface density. Appropriate gram weight ensures that the composite medium has appropriate porosity and high flux. At the same time, it also has good mechanical strength, high hardness, and is not too soft.

[0037] The distribution density of the second particles in the present invention can be determined by using a scanning electron microscope to characterize the cross-section of the composite medium and then selecting a certain area (e.g., 1 μm 2 (1μm times 1μm) or 100μm 2 (10 μm multiplied by 10 μm) or, the specific area size depends on the actual situation,) and then use computer software (such as Matlab, NIS-Elements, etc.) or manual measurement to obtain the number of second particles on the area, and obtain the distribution density value by calculation; perform several tests (preferably more than 10 times), take the average value, and thus obtain the distribution density of the second particles.

[0038] As a further improvement of the present invention, the support layer further includes third particles, the third particles are polyethylene materials, and the SEM average particle size of the third particles is 8-80 μm.

[0039] In some fields, we hope to increase the flux (air permeability) of the composite medium as much as possible, that is, we hope that the porosity of the composite medium (especially the porosity of the support layer) is large; in the present invention, we want to increase the porosity of the support layer and even the composite medium as a whole by adding suitable third particles; then what kind of third particles can increase the porosity? After research, firstly, the third particles need to be polyethylene materials, which have good similarity and compatibility with the second particles, are easy to mix evenly, and will not have the phenomenon of "powder inclusion", and will not affect the hardness and compressive strength of the composite medium; at the same time, by adjusting the SEM average particle size of the third particles to 8-80μm, the third particles of such a particle size will easily approach the second particles and adhere to them, which will help to form more pores in the support layer, so that the support layer has a higher porosity and the flux of the composite medium is higher; at the same time, it basically does not affect the mechanical properties of the composite medium, and its compressive strength is still high.

[0040] As a further improvement of the present invention, the ratio of the SEM average particle size of the second particles to the SEM average particle size of the third particles is 5-35:1; and the SEM average particle size of the third particles is larger than the SEM average particle size of the first particles.

[0041] After research, it was found that when the ratio of the particle size of the second particles to the particle size of the third particles is regulated within an appropriate range, the third particles will be more likely to approach and adhere to the second particles, thereby forming more pores, which will further increase the flux of the composite medium; in addition, it should be noted that the particle size of the third particles cannot be too small, especially not smaller than the particle size of the first particles; if the particle size of the third particles is too small, it will easily affect the porosity and strength of the supporting layer, and then affect the flux and compressive strength of the composite medium.

[0042] As a further improvement of the present invention, the surface of the separation layer facing away from the support layer is the first surface, the surface of the support layer facing away from the separation layer is the second surface, and the hole area rate of the second surface is 10%-70%;

[0043] The ratio of the hole area ratio of the first surface to the hole area ratio of the second surface is 0.3-0.9:1.

[0044] When performing impurity interception filtration, the second surface is usually used as the liquid inlet surface and the first surface as the liquid outlet surface; since the second surface is the first area in the composite medium to contact the fluid, we hope that the pore area ratio of the second surface is relatively large, so as to facilitate the rapid passage of the fluid; but we do not want the pore area ratio of the second surface to be too large, otherwise it will easily reduce the compressive strength of the composite medium, and the particulate matter on the second surface will easily fall off, which will affect the purity of the fluid. After research, the pore area ratio of the second surface is adjusted to 10%-70%. At such a pore area ratio, on the one hand, it is convenient for the fluid to pass quickly, and at the same time The second surface has good resistance strength and can withstand pressure for a long time; and since the first surface is part of the separation layer, in order to ensure the interception efficiency, the pore area rate of the first surface will be relatively small (reflecting that the separation layer is relatively dense); but the pore area rate of the first surface cannot be too low, because in some applications, backwashing is required. If the pore area rate of the first surface is too low, it will affect the yield of impurities; through research, the ratio of the pore area rate of the first surface to the pore area rate of the second surface is controlled to be 0.3-0.9:1, which not only ensures the interception efficiency, but also facilitates backwashing, thereby obtaining a higher impurity yield. Through the synergistic effect between the pore area rate on the first outer surface and the pore area rate on the second outer surface, it is more conducive to making the composite medium have a larger flow rate, facilitating the rapid passage of the fluid through the composite medium, shortening the filtration time, and having a larger pressure resistance to meet the needs of practical applications.

[0045] In the present invention, the pore area ratio of the first surface and the second surface can be characterized by scanning electron microscopy on the surface of the porous medium, and then a certain area, such as 1 μm 2 (1μm times 1μm) or 100μm 2 (10μm multiplied by 10μm) or, the specific area size depends on the actual situation, and then use the corresponding computer software or manually measure the total area of ​​the holes in the area, calculate the hole area rate, conduct several tests (at least 10 times or more), and take the average value to obtain it.

[0046] As a further improvement of the present invention, the first surface has a plurality of mold wall contact areas, the SEM average width of the mold wall contact areas is 5-35 μm; the area rate of the mold wall contact areas is 10%-65%;

[0047] The area ratio of the mold wall contact area = the SEM area of ​​the mold wall contact area / the SEM area of ​​the first surface.

[0048] In the present invention, the mold wall contact area on the first surface is formed when the second particles contact the inner wall of the mold during the sintering process and are formed in the molten state during sintering (the mold wall contact area is equivalent to a part of the surface entity part, and is a smooth and flat surface formed by direct contact between the particles and the mold). The SEM average width of the mold wall contact area reflects to a certain extent the size of the skeleton material as the surface of the sintered porous material, and thus the compressive strength of the surface of the composite medium; by controlling the SEM average width of the mold wall contact area within the range of 5-35μm, the composite medium has a good skeleton foundation, which is beneficial for the second surface of the composite medium to have good compressive strength, especially for backwashing; the area ratio of the mold wall contact area represents the entity part of the contact between the second particles and the mold in the sintered composite medium, so the area ratio of the mold wall contact area will also affect the compressive strength of the composite medium surface during application to a certain extent; the present invention further makes the sintered composite medium have good compressive strength by controlling the area ratio of the mold wall contact area within the range of 10%-65%, and further improves the surface compressive strength of the composite medium during backwashing conditions.

[0049] As a further improvement of the present invention, the thickness of the composite medium is 10-50 mm; the interception efficiency of the composite medium for impurity particles with a particle size of 1-20 microns is not less than 80%;

[0050] The flux of the composite medium is 200-2000L / min@7kpa;

[0051] The Shore A hardness of the composite medium is not less than 70HA;

[0052] The compressive strength of the composite medium is not less than 300N.

[0053] The thickness of the composite medium can be measured by using a scanning electron microscope to characterize the morphology of the composite medium structure, and then using computer software (such as Matlab, NIS-Elements, etc.) or manual measurement to calculate (of course, it can also be tested with other testing instruments); when the thickness of the composite medium is too small, its mechanical strength will be low; at the same time, due to the short filtration time, effective filtration cannot be performed; when the thickness of the composite medium is too large, its filtration time will be too long, the time cost will be too high, and the overall flux size will be affected; the thickness of the composite medium of the present invention is 10-50mm, and under the combined effect of the ideal pore structure, it is ensured that the composite medium not only has a high mechanical strength, but also can be effectively filtered and has a high interception efficiency;

[0054] Through the interception test and the gas flux test, it is shown that the composite medium of the present invention not only has the ability to efficiently intercept various fine impurities, but also has a good flux; through the hardness and compressive strength tests, it is shown that the composite medium of the present invention has good hardness and compressive strength. On the one hand, it is suitable for various processing treatments, and on the other hand, it can be filtered, intercepted, and backwashed for a long time, so as to obtain more expensive impurities (such as precious metal catalysts).

[0055] The Shore A hardness of the composite medium can be tested by Shore A hardness tester, and the Shore A hardness of the composite medium can be obtained by taking the average value after three tests.

[0056] The flux of the composite medium can be tested by the following method: use an air permeability tester to test the air flux of the composite medium, adjust the air pressure to the test pressure, where the test pressure is 7kpa, read and record the data, and obtain the air flux of the composite medium, where the air permeability area of ​​the composite medium is controlled at 250cm 2 Under the conditions;

[0057] Compression strength test method: Cut the composite medium into a circular arch sample with a width of 1 cm and a length of 3 cm, place it on a servo tensile testing machine (model: HD-A513-C), and test the compression strength.

[0058] Furthermore, the present invention also provides a process for preparing an asymmetric gradient sintered composite medium, comprising the following steps:

[0059] S1, preparing material A and material B; the material A comprises first particles with a weight average molecular weight of 3 million to 8 million, the first particles are UPE, and the particle size of the first particles is less than 100 μm;

[0060] The material B comprises second particles with a weight average molecular weight of 200,000-800,000, the second particles are HDPE, and the particle size of the second particles is greater than 200 μm;

[0061] S2, primary sintering, first uniformly load material B into the sintering mold and compact it, then heat it to 150-180℃ at a heating rate of 3-10℃ / min, then keep it warm for 80-120min, and then cool it to 20-40℃;

[0062] S3, pre-treatment, then evenly load material A into the sintering mold and compact it, then heat it to 110-140℃, and then keep it warm for 20-50min;

[0063] S4, secondary sintering, then heating to 150-180°C, the holding time is 70%-95% of the holding time in S2,

[0064] S5, naturally cooling to obtain an asymmetric composite medium.

[0065] As a further improvement of the present invention, the material B further comprises a third particle having a weight average molecular weight of 2 million to 6 million, the third particle is UPE, and its bulk density is 0.15-0.25 g / cm 3 ; The mass fraction of the third particles in material B is 10%-40%.

[0066] As a further improvement of the present invention, in the primary sintering of S2, the temperature is first raised to 110-140°C, the holding time is 2-5 times the holding time in S3, and then the temperature is raised to 150-180°C.

[0067] As a further improvement of the present invention, the mass ratio of material A to material B in S1 is 1:3-8; the heating rate in S3 is 3-10°C / min; the heating rate in S4 is 60%-90% of the heating rate during the first sintering in S2.

[0068] When preparing the asymmetric gradient sintered composite medium of the present invention, material A and material B are first prepared, wherein material A is used to form a separation layer; and material B is used to form a support layer; since the pore size of the pores in the separation layer is relatively small, material A contains a first particle, the first particle is UPE, and the weight-average molecular weight is 3 million to 8 million, and the particle size is relatively small (generally, raw materials with smaller particle sizes are more likely to sinter into pores with smaller pore sizes), not exceeding 100 μm, and subsequently by combining the corresponding sintering process, it is beneficial to obtain a separation layer with an ideal pore size (the pore size of the separation layer is smaller), which is convenient for efficiently intercepting various Impurities, and the number of holes in the separation layer will not be too small, which will not affect the overall flux of the composite medium; and because the pores in the separation layer have a relatively large pore size, material B contains a second particle, and the second particle is HDPE (high-density polyethylene), with a weight-average molecular weight of 200,000-800,000, and a relatively large particle size greater than 200 μm. Subsequently, by combining the corresponding sintering process, it is beneficial to obtain an ideal support layer. The pores in the support layer have a large pore size and a large number of pores, which is beneficial to make the composite medium have a higher porosity and a higher overall flux; preferably, the bulk density of HDPE is not less than 0.4 g / cm 3 The higher density helps to ensure that the support layer has good mechanical strength despite the large internal pores, and the overall hardness and compressive strength of the medium are both high;

[0069] In addition, after research, it was found that on the basis of selecting such material A and material B, the mass ratio of material A to material B is preferably 1:3-8 (if material A is too much, the porosity of the entire composite medium will be low and the air permeability will be low. If material A is too little, the interception efficiency will be too low or the mechanical properties will be poor). With the corresponding sintering process, a composite medium with an ideal structure is obtained, so that the composite medium has high air permeability and high interception efficiency, and is conducive to ensuring the composite strength between layers. In some fields, we hope to increase the flux (air permeability) of the composite medium as much as possible, that is, we hope that the porosity of the composite medium (especially the porosity of the support layer) is large. After research, it was found that a small amount of third particles were added to material B (the mass fraction of the third particles in material B is 10%-40%, and the rest are second particles). The third particles are UPE, with a weight-average molecular weight of 2 million-6 million and a bulk density of 0.15-0.25 g / cm 3 ; By adding UPE with a relatively low bulk density to material B, and in combination with a certain sintering process, the third particle UPE will be mixed with the second particle HDPE to bond and melt, thereby forming more holes, further increasing the number of holes in the support layer, thereby improving the porosity of the support layer and even the composite medium as a whole; at the same time, the third particles are relatively small (holes with too large pores will not be sintered), so the mechanical strength of the support layer and even the composite medium as a whole is less affected;

[0070] At the same time, since both material A and material B are polyethylene materials with good compatibility, they are easy to form a composite layer of a certain thickness under the synergistic effect of a certain sintering process, thereby ensuring the composite strength of the composite medium (the layers are not easy to separate), so that the composite medium has high hardness and high compressive strength;

[0071] Preferably, after the materials A and B are prepared, they can be dried at a temperature of 50-80°C for 40-80 minutes. Drying is beneficial to remove the moisture contained in the materials A and B. If the moisture content in the materials is too high, the materials may agglomerate, which affects sintering and is not conducive to forming a composite medium with an ideal pore size and porosity.

[0072] After preparing material A and material B, the product is then sintered. Since an asymmetric composite gradient medium is to be prepared, a secondary sintering method is adopted in the present invention. The support layer is prepared first. When preparing the support layer, material B is first evenly loaded into the sintering mold and compacted, and then the temperature is increased. The heating rate is 3-10°C / min. Since material B mainly consists of large-diameter HDPE particles, at such a heating rate, on the one hand, the temperature of material B can be increased at a faster rate (but the particles will not shrink excessively due to the excessive heating rate), and on the other hand, it can ensure that most of the particles in material B are heated evenly, and the temperature difference between the particles will not be too large, which is beneficial to the subsequent sintering. Then, the temperature is kept at 150-180°C for 80-120 minutes. At such a sintering temperature and sintering insulation time, Under the interaction of the two, the particles in material B will melt with each other, and the adjacent particles will begin to stick together, and the support layer will be initially formed. The support layer will not be fully formed until the second sintering is completed; (After the first sintering, some particles will melt and stick together to form holes with a certain pore size; at the same time, some particles have not yet or are only initially stuck together;) Therefore, it should be noted that during the first sintering, it is not desirable for the support layer to be fully sintered, because if it is fully sintered at this time, then during the second sintering, the second particle in material B will be further sintered. At the same time, due to the small molecular weight of HDPE, the relatively high melt index and good fluidity, it is easy to "over-sinter" phenomenon, which will greatly reduce the number of holes in the support layer, and finally the porosity and air permeability (flux) of the composite medium are too low;

[0073] Preferably, during the first sintering, the temperature is not raised directly to 150-180°C (above the melting point), but first raised to 110-140°C (near the melting point, even if melt adhesion occurs between the particles, it is only a small amount, so that over-sintering will not occur, and this temperature is not much different from the final sintering temperature of 150-180°C) and kept warm for a period of time. The purpose of this is mainly to make the temperature between the particles almost the same, so as to facilitate subsequent sintering and sinter out holes with ideal pore size and number; especially when material B contains both the second particle and the third particle, such treatment is more necessary, because the second particle and the third particle must have different internal temperature rise rates under the same heating conditions (there is still a certain difference between HDPE and UPE). The difference between the two, in different areas of the mold, the heating effect on the particles is also different). If the temperature is directly raised to 150-180°C, there must be a certain temperature difference between some of the second particles and the third particles. If the temperature difference is too large, it will be detrimental to the subsequent sintering. By first keeping warm at 110-140°C, the temperature between the second particles and the third particles can be greatly reduced, and the temperature between the particles is almost the same, which is conducive to the subsequent sintering and ensures the various performances of the product. At the same time, due to the large mass of material B, the insulation time at 110-140°C also needs to be relatively long, and the insulation time is 2-5 times that of S3, preferably 100-150min, which can further ensure that the temperature of the particles in material B is basically the same.

[0074] After the support layer is initially sintered and formed, it is cooled to 20-40°C, and then the material A used to form the separation layer is evenly loaded into the sintering mold for compaction, and then heated to 110-140°C, followed by insulation for 20-50 minutes for pretreatment. The purpose of such pretreatment is to make the temperature of the particles in the support layer basically the same as the temperature of material A and the temperature between the particles in material A basically the same, which is conducive to subsequent sintering, thereby ensuring the formation of a composite layer of a certain thickness, and then ensuring the composite strength and compressive strength of the composite medium; and since the mass of material A is relatively small, the insulation time is relatively short at this time, only 20-50 minutes (too long insulation time is likely to affect the pore size and porosity of the support layer); preferably, the heating rate of S3 pretreatment is 3-10°C / min. Such a heating rate not only ensures efficiency, but also makes the temperature difference between the first particles of material A not too large. After the pretreatment, the temperature between the particles can be almost the same;

[0075] After the pretreatment, secondary sintering is performed, and the sintering temperature is still controlled to be raised to 150-180°C. At such a temperature, the surfaces of the first particles that have already bonded to each other will be further fused with each other due to the movement and diffusion of the molecular chain segments, and stably and firmly connected together; by controlling the sintering temperature and the holding time, the particles can be bonded while retaining some pores between the particles, and finally forming an ideal porous material; and the holding time when preparing the separation layer in the present invention is crucial. First of all, in order to make the entire composite medium have a higher flux, the separation layer must not be very thick, so the holding time is not expected to be too long. After research, the holding time is not expected to exceed the holding time of the first sintering, otherwise it will be over-sintered (both the separation layer and the support layer will be over-sintered), resulting in low porosity of the entire composite medium, small flux and low strength; and if the holding time is too short, then it will not be fully sintered, resulting in the separation layer The crystallinity is too high at this time, and there may still be "powder inclusions" and other phenomena in the entire composite medium. The separation layer and the support layer are not well combined, and the entire composite medium The composite strength and compressive strength are too low; after research, the insulation time of the second sintering is 70%-95% of the insulation time in S2 (the first sintering time, that is, the time to stay after heating to the highest temperature during the first sintering). Such insulation time and the corresponding sintering temperature can make the separation layer and the support layer fully sintered and perfectly combined, thereby ensuring that the entire composite medium has an ideal pore structure, high flux and interception efficiency, and a composite layer with a certain thickness, and the composite medium has good composite strength and compressive strength; preferably, the heating rate in S4 is 60%-90% of the heating rate during the first sintering of S2, thereby further ensuring that the temperature of the particles in the support layer is very close to the temperature of material A, and the temperature difference between the first particles in material A is also small, on the one hand, the pore size of the holes formed in the separation layer is relatively uniform, ensuring the interception efficiency; on the other hand, the bonding strength is guaranteed, a composite layer of a certain thickness is formed, and the entire composite medium has a high composite strength, which can meet the needs of practical applications;

[0076] After the secondary sintering, the medium is naturally cooled to obtain an asymmetric composite medium. The composite medium includes a support layer, a composite layer and a separation layer for intercepting various fine substances. The composite medium as a whole has a suitable pore size and porosity, and the layers are tightly combined, thereby ensuring that the composite medium has high interception efficiency and high flux while also having high composite strength (the separation layer and the support layer are not easy to separate), high hardness and high compressive strength. The composite medium is particularly suitable for the recovery of catalysts and precious metals (platinum and iridium, etc.).

[0077] Furthermore, the present invention also provides an application of an asymmetric gradient sintered composite medium, wherein the composite medium is used for recovering catalysts and precious metals.

[0078] As is well known, conventional phase conversion membranes are not hard enough and have insufficient pressure resistance, so they cannot meet the backwashing conditions (backwashing requires the product to have a certain pressure resistance to withstand the gas pressure during backwashing). The composite medium prepared in the present invention has high hardness and pressure resistance, and is mainly used in interception filtration and material recovery applications, especially catalyst (especially some expensive metal catalysts) recovery and precious metal platinum, iridium and palladium and other materials recovery, first intercepting the corresponding substances and then recovering them by inflating in the reverse direction.

[0079] Beneficial effects of the present invention: the asymmetric gradient sintered composite medium provided by the present invention includes a support layer, a composite layer and a separation layer for intercepting various fine substances; the composite medium has a suitable average pore size and porosity, thereby ensuring that the composite medium has a high interception efficiency and a high flux; at the same time, the composite layer has a suitable thickness and the separation layer has a certain degree of crystallinity, so that the layers are tightly combined, the composite medium has a high composite strength and a high compressive strength, and can be intercepted and filtered under a high pressure for a long time; further, since the separation layer includes a first particle for forming a porous structure; the support layer includes a second particle for forming a porous structure, by controlling the particle size of the first particle and the second particle, as well as the thickness of the separation layer, the composite medium is suitable for backwashing, and can have a good yield of intercepted impurities, so it is particularly suitable for the recovery of expensive catalysts and precious metals (platinum and iridium, etc.). The preparation method provided by the present invention can conveniently, quickly and effectively prepare the above-mentioned asymmetric gradient sintered composite medium. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] The present invention will be further described below in conjunction with the accompanying drawings:

[0081] Figure 1 This is a schematic diagram of the SEM of the composite layer area on the cross section of the sintered composite medium prepared in Example 1, with a magnification of 200×; the red boxes are the connection nodes

[0082] Figure 2 This is a schematic diagram of a scanning electron microscope of the support layer region on the cross section of the sintered composite medium prepared in Example 1, wherein the magnification is 100×;

[0083] Figure 3 This is a schematic diagram of a scanning electron microscope on the first surface of the sintered composite medium prepared in Example 6, wherein the magnification is 200×; wherein the red circle is the mold wall contact area;

[0084] Figure 4 This is a schematic diagram of a scanning electron microscope on the second surface of the sintered composite medium prepared in Example 6, wherein the magnification is 50×;

[0085] Figure 5This is a schematic diagram of a SEM image of the separation layer region on the cross section of the sintered composite medium prepared in Example 6, wherein the magnification is 200×;

[0086] Figure 6 This is a schematic diagram of a scanning electron microscope of a composite layer region on a cross section of a sintered composite medium prepared in Example 6, wherein the magnification is 50×;

[0087] Figure 7 This is a schematic diagram of a SEM image of the separation layer region on the cross section of the sintered composite medium prepared in Example 2, wherein the magnification is 100×;

[0088] Figure 8 This is a schematic diagram of a scanning electron microscope of a composite layer region on a cross section of a sintered composite medium prepared in Example 2, wherein the magnification is 100×;

[0089] Fig. 9 This is a schematic diagram of a scanning electron microscope of the support layer region on the cross section of the sintered composite medium prepared in Example 2, wherein the magnification is 50×;

[0090] Fig.10 This is a schematic diagram of a SEM image of the separation layer region on the cross section of the sintered composite medium obtained in Example 7, wherein the magnification is 50×;

[0091] Fig.11 This is a schematic diagram of a scanning electron microscope of a composite layer region on a cross section of a sintered composite medium prepared in Example 7, wherein the magnification is 100×;

[0092] Fig.12 This is a schematic scanning electron microscope image of the support layer region on the cross section of the sintered composite medium obtained in Example 7, where the magnification is 50×. DETAILED DESCRIPTION

[0093] The present invention is further described in detail below in conjunction with the examples. Unless otherwise specified, in the following examples, the raw materials and equipment used to prepare the sintered composite medium can be purchased through commercial channels.

[0094] Embodiment 1 A process for preparing an asymmetric gradient sintered composite medium comprises the following steps:

[0095] S1, preparing material A and material B; wherein material A comprises first particles with a weight average molecular weight of 4.2 million, the first particles are UPE, and the particle size of the first particles is less than 100 μm; wherein material B comprises second particles with a weight average molecular weight of 450,000, the second particles are HDPE, and the particle size of the second particles is greater than 200 μm;

[0096] The mass ratio of material A to material B is 1:7;

[0097] S2, primary sintering, first uniformly load material B into the sintering mold and compact it, first heat it to 125℃, keep it warm for 120min, and the heating rate is 5℃ / min; then heat it to 160℃, the heating rate is 5℃ / min, then keep it warm for 100min, and then cool it to 30℃;

[0098] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 135°C at a heating rate of 5°C / min, and then keep it warm for 30 minutes;

[0099] S4, secondary sintering, then heating to 175 °C, heating rate is 4 °C / min, and the holding time is 90 min;

[0100] S5, naturally cooling to obtain an asymmetric composite medium.

[0101] Example 2 A process for preparing an asymmetric gradient sintered composite medium comprises the following steps:

[0102] S1, preparing material A and material B; wherein material A comprises first particles with a weight average molecular weight of 4.5 million, the first particles are UPE, and the particle size of the first particles is less than 100 μm; wherein material B comprises second particles with a weight average molecular weight of 500,000, the second particles are HDPE, and the particle size of the second particles is greater than 200 μm;

[0103] The mass ratio of material A to material B is 1:6;

[0104] S2, primary sintering, first uniformly load material B into the sintering mold and compact it, first heat it to 120℃, keep it for 110min, and the heating rate is 6℃ / min; then heat it to 160℃, the heating rate is 6℃ / min, then keep it for 95min, and then cool it to 30℃;

[0105] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 135°C at a heating rate of 5°C / min, and then keep it warm for 30 minutes;

[0106] S4, secondary sintering, then heating to 175 °C, heating rate is 4 °C / min, and the holding time is 85 min;

[0107] S5, naturally cooling to obtain an asymmetric composite medium.

[0108] Example 3 A process for preparing an asymmetric gradient sintered composite medium comprises the following steps:

[0109] S1, preparing material A and material B; wherein material A comprises first particles with a weight average molecular weight of 5 million, the first particles are UPE, and the particle size of the first particles is less than 100 μm; wherein material B comprises second particles with a weight average molecular weight of 550,000, the second particles are HDPE, and the particle size of the second particles is greater than 200 μm;

[0110] The mass ratio of material A to material B is 1:5;

[0111] S2, primary sintering, first uniformly load material B into the sintering mold and compact it, first heat it to 120℃, keep it for 105min, and the heating rate is 8℃ / min; then heat it to 170℃, the heating rate is 8℃ / min, then keep it for 90min, and then cool it to 30℃;

[0112] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 135°C at a heating rate of 5°C / min, and then keep it warm for 40 minutes;

[0113] S4, secondary sintering, then heating to 175 °C, heating rate is 6 °C / min, and the holding time is 82 min;

[0114] S5, naturally cooling to obtain an asymmetric composite medium.

[0115] Example 4 A process for preparing an asymmetric gradient sintered composite medium comprises the following steps:

[0116] S1, preparing material A and material B; wherein material A comprises first particles with a weight average molecular weight of 6 million, the first particles are UPE, and the particle size of the first particles is less than 100 μm; wherein material B comprises second particles with a weight average molecular weight of 650,000, the second particles are HDPE, and the particle size of the second particles is greater than 200 μm;

[0117] The mass ratio of material A to material B is 1:4;

[0118] S2, primary sintering, first uniformly load material B into the sintering mold and compact it, first heat it to 115℃, keep it for 95min, and the heating rate is 6℃ / min; then heat it to 170℃, the heating rate is 6℃ / min, then keep it for 100min, and then cool it to 40℃;

[0119] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 135°C at a heating rate of 5°C / min, and then keep it warm for 30 minutes;

[0120] S4, secondary sintering, then heating to 175 °C, heating rate is 4 °C / min, and the holding time is 80 min;

[0121] S5, naturally cooling to obtain an asymmetric composite medium.

[0122] Example 5 A process for preparing an asymmetric gradient sintered composite medium comprises the following steps:

[0123] S1, preparing material A and material B; wherein material A comprises first particles with a weight average molecular weight of 7 million, the first particles are UPE, and the particle size of the first particles is less than 100 μm; wherein material B comprises second particles with a weight average molecular weight of 800,000, the second particles are HDPE, and the particle size of the second particles is greater than 200 μm;

[0124] The mass ratio of material A to material B is 1:3;

[0125] S2, primary sintering, first uniformly load material B into the sintering mold and compact it, first heat it to 115℃, keep it for 90min, and the heating rate is 6℃ / min; then heat it to 160℃, the heating rate is 6℃ / min, then keep it for 95min, and then cool it to 30℃;

[0126] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 135°C at a heating rate of 5°C / min, and then keep it warm for 30 minutes;

[0127] S4, secondary sintering, then heating to 175 °C, heating rate is 4 °C / min, and the holding time is 70 min;

[0128] S5, naturally cooling to obtain an asymmetric composite medium.

[0129] Example 6 A process for preparing an asymmetric gradient sintered composite medium comprises the following steps:

[0130] S1, prepared with material A and material B; wherein the first particle selected from material A is the same as that in Example 1, material B comprises second particles and third particles, wherein the second particles are the same as those in Example 1; the weight average molecular weight of the third particle is 3 million, the third particle is UPE, and its bulk density is 0.18 g / cm 3 ; The mass fraction of the third particle in material B is 20%; the mass ratio of material A to material B is 1:7;

[0131] S2, primary sintering, firstly, material B is uniformly loaded into the sintering mold and compacted, firstly, the temperature is raised to 120℃, the holding time is 125min, the heating rate is 5℃ / min; then the temperature is raised to 160℃, the heating rate is 5℃ / min, then the temperature is held for 115min, and then cooled to 30℃;

[0132] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 135°C at a heating rate of 5°C / min, and then keep it warm for 40 minutes;

[0133] S4, secondary sintering, then heating to 165 °C, heating rate is 4 °C / min, and the holding time is 100 min;

[0134] S5, naturally cooling to obtain an asymmetric composite medium.

[0135] Example 7 A process for preparing an asymmetric gradient sintered composite medium comprises the following steps:

[0136] S1, prepare material A and material B; wherein the first particle selected from material A is the same as that in Example 2, material B comprises second particles and third particles, wherein the second particles are the same as those in Example 2; the weight average molecular weight of the third particles is 4 million, the third particles are UPE, and the bulk density is 0.22 g / cm3; the mass fraction of the third particles in material B is 30%; the mass ratio of material A to material B is 1:6;

[0137] S2, primary sintering, first uniformly load material B into the sintering mold and compact it, first heat it to 125℃, keep it at this temperature for 120min, and the heating rate is 6℃ / min; then heat it to 160℃, the heating rate is 6℃ / min, and then keep it at this temperature for 110min, and then cool it to 30℃;

[0138] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 130°C at a heating rate of 5°C / min, and then keep it warm for 40 minutes;

[0139] S4, secondary sintering, then heating to 165 °C, heating rate is 4 °C / min, and the holding time is 95 min;

[0140] S5, naturally cooling to obtain an asymmetric composite medium.

[0141] Comparative Example 1 A preparation process of an asymmetric gradient sintered composite medium comprises the following steps:

[0142] S1, preparing material A and material B; wherein the first particles selected for material A are the same as those in Example 1, and the second particles selected for material B are the same as those in Example 1; the mass ratio of material A to material B is 1:7;

[0143] S2, primary sintering, first uniformly load material B into the sintering mold and compact it, directly heat it to 160℃ at a heating rate of 10℃ / min, then keep it warm for 30min, and then cool it to 30℃;

[0144] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 135°C at a heating rate of 5°C / min, and then keep it warm for 10 minutes;

[0145] S4, secondary sintering, then heating to 160 °C, heating rate is 10 °C / min, and the holding time is 20 min;

[0146] S5, naturally cooling to obtain an asymmetric composite medium.

[0147] Compared with the sample prepared in Example 1, the average pore size of PMI of the sample prepared in Comparative Example 1 is too large, and the interception efficiency of 1 μm impurities is very low, which is not practical.

[0148] Comparative Example 2 A preparation process of an asymmetric gradient sintered composite medium comprises the following steps:

[0149] S1, preparing material A and material B; wherein the first particles selected for material A are the same as those in Example 1, and the second particles selected for material B are the same as those in Example 1; the mass ratio of material A to material B is 1:7;

[0150] S2, primary sintering, firstly, material B is uniformly loaded into the sintering mold and compacted, then directly heated to 160°C at a heating rate of 2°C / min, then kept at this temperature for 220min, and then cooled to 30°C;

[0151] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 135°C at a heating rate of 5°C / min, and then keep it warm for 60min;

[0152] S4, secondary sintering, then heating to 190 °C, heating rate is 2 °C / min, and the holding time is 180 min;

[0153] S5, naturally cooling to obtain an asymmetric composite medium.

[0154] Compared with the sample prepared in Example 1, the sample prepared in Comparative Example 1 has very low porosity, very low air flux, poor filtration efficiency, and is not practical.

[0155] Comparative Example 3 A preparation process of an asymmetric gradient sintered composite medium comprises the following steps:

[0156] S1, preparing material A and material B; wherein the first particles selected for material A are the same as those in Example 1, and the second particles selected for material B are the same as those in Example 1; the mass ratio of material A to material B is 1:7;

[0157] S2, primary sintering, firstly, material B is uniformly loaded into the sintering mold and compacted, and the temperature is raised to 160°C at a heating rate of 5°C / min, followed by heat preservation for 100min, and then cooled to 30°C;

[0158] S3, secondary sintering, then evenly load material A into the sintering mold and compact it, then heat it to 179°C, the heating rate is 10°C / min, and the holding time is 90min;

[0159] S4, natural cooling to obtain an asymmetric composite medium.

[0160] Compared with the sample prepared in Example 1, the sample prepared in Comparative Example 3 has almost no composite layer, and its hardness and compressive strength are very small. The separation layer and the support layer are easily separated under a very small external force, and it is impossible to intercept impurities, and it is even more impossible to backwash and recover impurities, so it is not practical.

[0161] Table 1

[0162]

[0163]

[0164] In the above table, the composite layer thickness of Example 7 does not fall within the protection range of the more preferred composite layer thickness, which will affect the overall flux to a certain extent, making the flux of the composite medium slightly worse; at the same time, its hardness and compressive strength are almost not increased.

[0165] Table 2

[0166]

[0167] Table 3

[0168]

[0169]

[0170] The samples prepared in Examples 1-5 were subjected to interception performance tests (in fact, the impurity particle size used in Example 1, Example 6, Comparative Example 1 and Comparative Example 2 was 1 micron, the impurity particle size used in Example 2 and Example 7 was 3 microns, the impurity particle size used in Example 3 was 5 microns, the impurity particle size used in Example 4 was 10 microns, and the impurity particle size used in Example 5 was 20 microns), air flux test, compressive strength test and Shore A hardness test, and the test results are shown in Table 4 below:

[0171] Retention efficiency Flux L / min@7kpa Compressive strength / N Shore A hardness / HA Example 1 More than 90% 520 500 93 Example 2 More than 90% 710 480 90 Example 3 More than 90% 950 460 87 Example 4 More than 90% 1260 440 84 Example 5 More than 90% 1700 400 80 Example 6 More than 90% 620 495 92 Example 7 More than 90% 820 475 89 Comparative Example 1 25% 580 250 65 Comparative Example 2 More than 90% 100 460 90

[0172] It can be seen from the above table that the composite media prepared in Examples 1-5 have a suitable pore size and porosity, which enables them to fully capture impurities of a certain particle size and ensure the interception efficiency, while also having a good flux, and high hardness and compressive strength; compared with Example 1, Example 6 adds a third particle during sample preparation, so that the flux of the composite medium is significantly improved, but the interception efficiency, hardness and compressive strength are almost unchanged; compared with Example 2, Example 7 adds a third particle during sample preparation, so that the flux of the composite medium is significantly improved, but the interception efficiency, hardness and compressive strength are almost unchanged.

[0173] Example 8 A process for preparing an asymmetric gradient sintered composite medium comprises the following steps:

[0174] S1, preparing material A and material B; wherein the first particles selected for material A are the same as those in Example 1, and the second particles selected for material B are the same as those in Example 1; the mass ratio of material A to material B is 1:7;

[0175] S2, primary sintering, first uniformly load material B into the sintering mold and compact it, directly heat it to 160℃ at a heating rate of 5℃ / min, then keep it warm for 120min, and then cool it to 30℃;

[0176] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 135°C at a heating rate of 5°C / min, and then keep it warm for 50min;

[0177] S4, secondary sintering, then heating to 180 °C, heating rate is 2 °C / min, and the holding time is 105 min;

[0178] S5, naturally cooling to obtain an asymmetric composite medium.

[0179] Compared with the sample prepared in Example 1 (the SEM average particle size of the first particles is 12 μm and the SEM average particle size of the second particles is 200 μm), the sample prepared in Example 8 was finally tested and the SEM average particle size of the first particles was 4.5, the SEM average particle size of the second particles was 180 μm, and the ratio of the SEM average particle size of the second particles to the SEM average particle size of the first particles was 40; the particle size of the first particles was relatively small, so that the gas flux of the sample prepared in Example 8 was 300 L / min@7kpa, which was significantly lower than that of the sample in Example 1; at the same time, it was found that if the sample was backwashed, the first particles would fall off relatively easily, which would affect the purity of the fluid and shorten the service life of the composite medium.

[0180] Example 9 A process for preparing an asymmetric gradient sintered composite medium comprises the following steps:

[0181] S1, preparing material A and material B; wherein the first particles selected for material A are the same as those in Example 1, and the second particles selected for material B are the same as those in Example 1; the mass ratio of material A to material B is 1:7;

[0182] S2, primary sintering, firstly, material B is uniformly loaded into the sintering mold and compacted, and then directly heated to 160°C at a heating rate of 5°C / min, then kept at this temperature for 100min, and then cooled to 30°C;

[0183] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 135°C at a heating rate of 5°C / min, and then keep it warm for 30 minutes;

[0184] S4, secondary sintering, then heating to 170 °C, heating rate is 5 °C / min, and the holding time is 70 min;

[0185] S5, naturally cooling to obtain an asymmetric composite medium.

[0186] Compared with the sample prepared in Example 1 (the SEM average width of the connection node is 10 μm, and the thickness of the composite layer is 100 μm), the sample prepared in Example 9 was finally tested and it was found that there were almost no connection nodes on its cross section. At the same time, the thickness of the composite layer was 45 μm, so that the compressive strength of the sample prepared in Example 9 was 470 / N and the Shore A hardness was 85HA. Compared with the compressive strength and Shore A hardness of the sample in Example 1, there were significant decreases, and there were certain problems during high-pressure backwashing.

[0187] Example 10 A process for preparing an asymmetric gradient sintered composite medium comprises the following steps:

[0188] S1, preparing material A and material B; wherein the first particles selected for material A are the same as those in Example 1, and the second particles selected for material B are the same as those in Example 1; the mass ratio of material A to material B is 1:2;

[0189] S2, primary sintering, first uniformly load material B into the sintering mold and compact it, directly heat it to 160℃, the heating rate is 10℃ / min, then keep it warm for 100min, and then cool it to 30℃;

[0190] S3, pretreatment, then evenly load material A into the sintering mold and compact it, then heat it to 135°C at a heating rate of 10°C / min, and then keep it warm for 30 minutes;

[0191] S4, secondary sintering, then heating to 175 °C, heating rate is 10 °C / min, and the holding time is 90 min;

[0192] S5, naturally cooling to obtain an asymmetric composite medium.

[0193] Compared with the sample prepared in Example 1 (separation layer thickness of 2 mm, overall thickness of 15 mm), Example 10 uses more material A in the separation layer, resulting in a thicker separation layer of 6 mm and an overall thickness of 15 mm. The ratio of the thickness of the separation layer to the thickness of the composite medium is 40%, so that the gas flux of the sample prepared in Example 8 is 350 L / min@7kpa, which is significantly lower than that of the sample in Example 1, while the interception efficiency is not significantly improved. At the same time, it is found that when the sample is backwashed, the intercepted impurities are difficult to be backwashed out, and the recovery rate of the impurities is very low, which is not conducive to the recovery of catalysts and precious metals.

[0194] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. An asymmetric gradient sintered composite medium, comprising a main body, wherein the main body has a non-directional tortuous passage, characterized in that: The main body includes a support layer, a composite layer and a separation layer for intercepting various fine substances; the composite layer is located between the support layer and the separation layer; the average pore size of the separation layer is smaller than the average pore size of the support layer; The separation layer includes first particles for forming a porous structure; the support layer includes second particles for forming a porous structure; the composite layer includes first particles and second particles for forming a porous structure; the first particles and the second particles are both polyethylene materials; The thickness of the composite layer is not less than 0.1 μm, and the crystallinity of the separation layer is 40%-85%; The average pore size of the PMI of the composite medium is 0.1-25 μm, and the overall porosity of the composite medium is 25%-75%.

2. The asymmetric gradient sintered composite medium according to claim 1, characterized in that: The SEM average particle size of the first particles is 5-60 μm, and the SEM average particle size of the second particles is 80-500 μm.

3. The asymmetric gradient sintered composite medium according to claim 1, characterized in that: The thickness of the composite layer is 1-1000 μm, preferably, the thickness of the composite layer is 10-800 μm; more preferably, the thickness of the composite layer is 50-500 μm; In the composite layer, connection nodes are formed between the first particles and the second particles, and the SEM average width of the connection nodes is 3-50 μm.

4. The asymmetric gradient sintered composite medium according to claim 3, characterized in that: The ratio of the SEM average particle size of the second particles to the SEM average particle size of the first particles is 5-30; The ratio of the SEM average width of the connection node to the SEM average particle size of the first particle is 1:1.1-4.

5. The asymmetric gradient sintered composite medium according to claim 1, characterized in that: The thickness of the separation layer is 0.1-5 mm, and the ratio of the thickness of the separation layer to the thickness of the composite medium is 1%-20%.

6. The asymmetric gradient sintered composite medium according to claim 1, characterized in that: The distribution density of the second particles is 1-30 / 1mm 2 The composite medium has a gram weight of 0.5-1.2 g / cm 2 .

7. The asymmetric gradient sintered composite medium according to claim 1, characterized in that: The support layer also includes third particles, which are polyethylene materials, and the SEM average particle size of the third particles is 8-80 μm.

8. The asymmetric gradient sintered composite medium according to claim 7, characterized in that: The ratio of the SEM average particle size of the second particles to the SEM average particle size of the third particles is 5-35:1; and the SEM average particle size of the third particles is larger than the SEM average particle size of the first particles.

9. The asymmetric gradient sintered composite medium according to claim 1, characterized in that: The surface of the separation layer facing away from the support layer is the first surface, the surface of the support layer facing away from the separation layer is the second surface, and the hole area rate of the second surface is 10%-70%; The ratio of the hole area ratio of the first surface to the hole area ratio of the second surface is 0.3-0.9:

1.

10. The asymmetric gradient sintered composite medium according to claim 9, characterized in that: The first surface has a plurality of mold wall contact areas, the SEM average width of the mold wall contact areas is 5-35 μm; the area rate of the mold wall contact areas is 10%-65%; The area ratio of the mold wall contact area = the SEM area of ​​the mold wall contact area / the SEM area of ​​the first surface.

11. The asymmetric gradient sintered composite medium according to claim 1, characterized in that: The thickness of the composite medium is 10-50 mm; The composite medium has a retention efficiency of not less than 80% for impurity particles with a particle size of 1-20 microns; The flux of the composite medium is 200-2000L / min@7kpa; The Shore A hardness of the composite medium is not less than 70HA; The compressive strength of the composite medium is not less than 300N.

12. A process for preparing an asymmetric gradient sintered composite medium according to any one of claims 1 to 11, characterized in that: The following steps are involved: S1, equipped with material A and material B; The material A comprises first particles with a weight average molecular weight of 3 million to 8 million, the first particles are UPE, and the particle size of the first particles is less than 100 μm; The material B comprises second particles with a weight average molecular weight of 200,000-800,000, the second particles are HDPE, and the particle size of the second particles is greater than 200 μm; S2, primary sintering, first uniformly load material B into the sintering mold and compact it, then heat it to 150-180℃ at a heating rate of 3-10℃ / min, then keep it warm for 80-120min, and then cool it to 20-40℃; S3, pre-treatment, then evenly load material A into the sintering mold and compact it, then heat it to 110-140℃, and then keep it warm for 20-50min; S4, secondary sintering, then heating to 150-180°C, the holding time is 70%-95% of the holding time in S2, S5, natural cooling, to obtain an asymmetric composite medium.

13. The process for preparing an asymmetric gradient sintered composite medium according to claim 12, characterized in that: The material B further comprises a third particle having a weight average molecular weight of 2 million to 6 million, the third particle is UPE, and its bulk density is 0.15-0.25 g / cm 3 ; The mass fraction of the third particles in material B is 10%-40%.

14. The process for preparing an asymmetric gradient sintered composite medium according to claim 12, characterized in that: In the primary sintering of S2, the temperature is first raised to 110-140°C, the holding time is 2-5 times the holding time in S3, and then the temperature is raised to 150-180°C.

15. The process for preparing an asymmetric gradient sintered composite medium according to claim 12, characterized in that: The mass ratio of material A to material B in S1 is 1:3-8; the heating rate in S3 is 3-10°C / min; the heating rate in S4 is 60%-90% of the heating rate during the first sintering in S2.

16. The use of an asymmetric gradient sintered composite medium according to any one of claims 1 to 11, characterized in that: The composite medium is used for recovery of catalysts and recovery of precious metals.

Citation Information

Patent Citations

  • Manufacturing method of microporous membrane sinter filter element

    CN103071400A

  • Filtration media

    CN103429310A

  • UPE porous membrane with low specific surface area as well as preparation method and application of UPE porous membrane

    CN113926322A

  • Self-assembled asymmetric porous membrane and preparation method thereof

    CN117753225A

  • Pure-phase silicon carbide ultrafiltration membrane and one-step co-firing preparation method thereof

    CN117839456A